Eosinophils: old cells, new directions - Sanchez Santos, Alejandra; Socorro Avila, Iovanna; Galvan Fernandez, Helena; Cazorla Rivero, Sara; Lemes Castellano, Angelina; Cabrera Lopez, Carlos (Frontiers in Medicine, 2025)
Eosinophils are polymorphonuclear cells that have progressively gained attention due to their involvement in multiple diseases and, more recently, in various homeostatic processes. Their well-known roles range from asthma and parasitic infections to less prevalent diseases such as eosinophilic granulomatosis with polyangiitis, eosinophilic esophagitis, and hypereosinophilic syndrome. In recent years, various biological therapies targeting these cells have been developed, altering the course of eosinophilic pathologies. Recent research has demonstrated differences in eosinophil subtypes and their functions. The presence of distinct classes of eosinophils has led to the theory of resident eosinophils (rEos) and inflammatory eosinophils (iEos). Subtype differences are determined by the pattern of protein expression on the cell membrane and the localization of eosinophils. Most of this research has been conducted in murine models, but several studies confirm these findings in peripheral blood and tissue. The objective of this review is to provide a comprehensive analysis of eosinophils, by recent findings that divide this cell line into two distinct populations with different functions and purposes.